ANALISIS PENGARUH KEPUASAN KERJA TERHADAP KOMITMEN PROFESI DENGAN KOLEKTIVISME SEBAGAI VARIABEL MODERASI (Studi pada BPK RI Perwakilan Provinsi Jawa Tengah) - Widiyanto, Baharudin Yusuf (Diponegoro Journal of Management, 2017)
This study aims to examine the effect of job satisfaction on profession commitment as auditor with collectivism as moderation variable. This study was conducted at BPK RI Central Java Representation as an institution that applied mutation system. To determine samples, this study used purposive sampling and selected 50 auditors as respondents. Analysis method which used in this study are reliability test, validity test, classical assumptions test, Moderated Regression Analysis (MRA), coefficient determination test and hypothesis test. The results of this study indicate that job satisfaction has possitive significant effect to profession commitment, but collectivism can’t moderate job satisfaction to profession commitment. The result of coefficient determination indicate that independent and moderation variables can contribute 49,4% of profession commitment. The remaining 50,6% is influenced by another variables outside this study.